AI-driven biometric CAPTCHA: defending against automated ‎threats in web security - Bora, Dr. Neha; Bora , Pradyumna M.; Tidake, Dr. Vaishali S.; Dhomse , Ghanshyam P.; Pawar , Deepali P. (International Journal of Basic and Applied Sciences, 2025)
Web security is a critical aspect of modern life, as the increasing reliance on internet services exposes systems to various cyber threats. Au-‎Automated hacking tools exploiting registration systems with false information often led to bandwidth issues and Distributed Denial of Service ‎‎(DDoS) attacks. CAPTCHA remains a widely used mechanism for distinguishing between humans and automated systems. However, simple ‎CAPTCHAs are easily bypassed by advanced AI, while complex ones can frustrate genuine users. This research presents an innovative ‎B3DA (Biometric 3D Animated) CAPTCHA algorithm that integrates AI for Face Recognition with randomly generated Three-dimensional ‎animated characters. The proposed solution creates CAPTCHAs that are intuitive for people to handle but pose significant challenges in the ‎context of automated systems. By combining handwritten 3D animated characters into randomized strings, the B3DA CAPTCHA algorithm enhances security and usability. Experimental results validate the algorithm's robustness against bot-driven attacks, demonstrating its ‎ability to withstand sophisticated breaches while leveraging machine learning for continuous improvement. The B3DA CAPTCHA algorithm offers a transformative approach to CAPTCHA design, effectively balancing user convenience and resistance to automated hacking ‎tools, marking a significant advancement in web security solutions‎.
Keywords: Artificial Intelligence; B3DA; CAPTCHA; DDOS; OCR.